2004
DOI: 10.1021/jo048389m
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Highly Selective Chiral Auxiliary for the Asymmetric Synthesis ofl- andd-α-Amino Acid Derivatives via a Multicomponent Ugi Reaction

Abstract: This paper describes the synthesis of a bicyclic beta-amino acid scaffold in both pure enantiomeric forms and its application as chiral auxiliary in an intramolecular version of the Ugi multicomponent reaction (U-5C-4CR) to prepare alpha-amino acid derivatives of both D- and L-series in a straightforward and very stereoselective manner. The mild conditions required for the Ugi condensation and for the removal of the chiral auxiliary make this method very attractive to prepare a wide range of differently struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(37 citation statements)
references
References 17 publications
1
36
0
Order By: Relevance
“…The oxanorbornene derivative 26 (Scheme 9) also behaved in the same manner. Although its synthesis was more complex, [32] the additional value of the double bond will become evident below.…”
Section: Norbornane/ene Amino Acids As Bifunctional Building Blocks Imentioning
confidence: 99%
See 1 more Smart Citation
“…The oxanorbornene derivative 26 (Scheme 9) also behaved in the same manner. Although its synthesis was more complex, [32] the additional value of the double bond will become evident below.…”
Section: Norbornane/ene Amino Acids As Bifunctional Building Blocks Imentioning
confidence: 99%
“…In analogy with the approach illustrated in Section 3, we first investigated the use of the bicycles 26 as chiral auxiliaries and found that the optically pure α-aminoamides 47 (Scheme 17) could be conveniently obtained by a simple two-step procedure involving retro-Diels-Alder reactions of Ugi adducts 29 with loss of furan and acid-mediated cleavage of the resulting enamines 46. [32] Scheme 17. Ugi-mediated synthesis of enantiomerically pure α-amino acid derivatives through employment of an oxanorbornenyl chiral auxiliary.…”
Section: Applications Of the Ugi-derived Norbornane/ Norbornene Derivmentioning
confidence: 99%
“…Leaving aside previous work from our group, 3,4 to the best of our knowledge there are no references on the preparation of chiral 7-oxanitronorbornenes. 5 Moreover, they could not be synthesized from chiral nitroacrylates as dienophiles, 6 and only a few amines resulting from the reduction of racemic 7-oxanitronorbornenes have been resolved. 5 On the other hand, sugar derivatives with a furan ring in their structures have received attention as precursors in the preparation of biologically important compounds, such as tunicamines (main component of numerous antibiotics), 7 C-nucleosides, 8 peptidomimetics, 9 and spiro carbon linked disaccharides.…”
Section: Introductionmentioning
confidence: 99%
“…5 Moreover, they could not be synthesized from chiral nitroacrylates as dienophiles, 6 and only a few amines resulting from the reduction of racemic 7-oxanitronorbornenes have been resolved. 5 On the other hand, sugar derivatives with a furan ring in their structures have received attention as precursors in the preparation of biologically important compounds, such as tunicamines (main component of numerous antibiotics), 7 C-nucleosides, 8 peptidomimetics, 9 and spiro carbon linked disaccharides. 10 In most cases, furyl sugars can be prepared by either treatment of activated furans with the appropriate acceptors, 7,8a,10,11 or building the furan moiety from non-furylic precursors.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Amido-or amino ketone derivatives are important for their biological, pharmaceutical properties, 9,10 and in the preparation of antibiotic drugs such as nikomycine or neopolyoxines. 11,12 The common procedure for the synthesis of these class compounds is the Dakin-West reaction [13][14][15] which involves the condensation of α-amino acids with acetic anhydride in the presence of suitable base, [3][4][5][6][7][8][9][10][11][12][13][14][15][16] these reaction produce α-acetamido ketones ZnO, 29 Amberlyst-15, 30 iodine 31 and FeCl 3 .6H 2 O. 32 Ferric salts have applied for the formation of carbon-nitrogen and carbon-oxygen bonds in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%